Una biografia per la cittadinanza (Altre Modernità, 2014)
Being able to recognize, understand and narrate one’s own biography, in its incipit, ruit and exit, which define everybody’s existential path, has become a dramatically difficult social emergency that must be addressed. In current times, in fact, it is possible to observe both a need/right to narrate one’s own autobiography and a civil right/duty of being educated at doing it. Being capable of narrating one’s own life history is not a spontaneous act anymore, because contemporary life swallows up all histories in addition to History itself. Understanding and elaborating the past, making oneself capable of narrating it and letting oneself be inspired by it to deepen the knowledge of the present as its possible outcome, is considered superfluous and useless. Why did this happen? We will try to list a series of complex, and often dramatic, factors behind it, even though we know well that they depend on endless reasons and on the perspective chosen to interpret them. Contemporary life needs new parameters to define identity and social rooting, which nowadays can neither be simply inherited, nor offered by a single territory or place. This rooting has become more like a dimension that must be “trained” inside oneself to turn into the ability of moving simultaneously in the various places of life and into the ability of opposing, in a dynamical way, one’s own inner firmness to the constant external movement: in other words, the ability of “linking” the events in one’s own life along a time continuum, while space is always changing.All this implies cultivating what we have defined as the inner citizenship, a proposal of secular ethics based on some “pieces of consciousness” (the consciousness of the complementary difference between male and female, the consciousness of the presence of History inside an individual’s biography, the consciousness of the need of an education to democracy, etc.) that make the person ready to exercise his/her rights/duties in view of an active citizenship. In order to do this a person must first be convinced of his/her value.